Analysis of the location of the fuel station in Sulaimani - حسن, بەیان علی; محمد, شاد حمید (Sulaimani Journal for Humanities, 2019)
The cities are the center of human life and their activities, these activities are tied to the population services and requires transportation factors. Cars is the most important factors in the cities, at the same times and need some services, it depends on number, quality, characteristics. This paper deals with the number, area, and history of building, spatial distribution of this service of patrol station in Sulaimani city. One of the conclusions is that: each car has (4 )hours and (42)minutes in a day to get service from this stations